2018
DOI: 10.1088/2043-6254/aad12d
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anticancer, anti-diabetic and catalytic activity of bio-conjugated metal nanoparticles

Abstract: Improvement of biological activities of medicinal plant in combination with metal nanoparticles is highly appealing. Herein, bio-conjugated AuNP and AgNP have been synthesized at room temperature using leaf extract of Saraca asoca a medicinal plant. Phytochemicals present in aqueous leaf extract of Saraca asoca, are acting as reducing, capping and stabilizing agent. The formation of nanoparticles is confirmed and characterized by different instrumental techniques like UV-visible and IR spectroscopy, SEM, TEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Similar observations were made by Satpathy et al (2018), where the green synthesis of AgNPs using P. tuberosa extracts enhanced the cytotoxicity against breast, ovarian, multidrug resistant and brain cancer cell lines [29]. Patra et al (2018) endorsed and suggested such improvement in biological activities in the medicinal plants when in combination with a metal nanoparticle. In this study, the bio-conjugation of AgNPs with Saraca asoca not just improved the anticancer, but also the antibacterial, antidiabetic as well as catalytic activities of the plant extract [30].…”
Section: Antibacterial Activity Of Agnps Prepared Using Tchebula Frusupporting
confidence: 66%
See 1 more Smart Citation
“…Similar observations were made by Satpathy et al (2018), where the green synthesis of AgNPs using P. tuberosa extracts enhanced the cytotoxicity against breast, ovarian, multidrug resistant and brain cancer cell lines [29]. Patra et al (2018) endorsed and suggested such improvement in biological activities in the medicinal plants when in combination with a metal nanoparticle. In this study, the bio-conjugation of AgNPs with Saraca asoca not just improved the anticancer, but also the antibacterial, antidiabetic as well as catalytic activities of the plant extract [30].…”
Section: Antibacterial Activity Of Agnps Prepared Using Tchebula Frusupporting
confidence: 66%
“…Patra et al (2018) endorsed and suggested such improvement in biological activities in the medicinal plants when in combination with a metal nanoparticle. In this study, the bio-conjugation of AgNPs with Saraca asoca not just improved the anticancer, but also the antibacterial, antidiabetic as well as catalytic activities of the plant extract [30]. Cytotoxicity and IC50 values of T. chebula extract (TCE), silver nanoparticles (AgNPs), and TCEmediated silver nanoparticles (TCE + AgNPs) treatment on human breast adenocarcinoma (MCF-7) cells.…”
Section: Antibacterial Activity Of Agnps Prepared Using Tchebula Frumentioning
confidence: 99%
“…The results of the X-ray diffraction pattern confirmed the formation of nanoparticles with strong and narrow bands of Bragg peaks and this may be due to the stabilization of the nanoparticles by M. indica seed extract. Saraca asoca leaf extract mediated synthesized AuNPs showed similar diffraction peaks confirming the crystalline nature and cubic structure of synthesized AuNPs [29].…”
Section: Zeta Potential Analysissupporting
confidence: 60%
“…Thus, dose manipulation of these nanoformulations would have the prospects in the therapeutic management of diabetes. Presently, around 51 FDA-approved nanoformulations are applied clinically as medicines and all these nanoformulations have been initially designed to improve physicochemical, pharmaceutical, and pharmacokinetic attributes of comprising drug molecules [360]. Considering these, it would be expected that the nanoformulations of naturally occurring hypoglycaemic agents will offer huge prospects through improving patient compliance, ensuring cost-effectiveness, and reducing toxicity in diabetes therapy in the future.…”
Section: Present Scenario and Future Perspectivementioning
confidence: 99%